Factors associated with the improvement of vocal fold movement: An analysis of LEMG and laryngeal CT parameters. Issue 1 (February 2015) - Mengsteab, Paulos Y.; Kwon, Jeong-Yi; Han, Tai Ryoon; Kwon, Tack Kyun; Kim, Deok-Ho; Kim, Sang Jun
Abstract The aim of this study is to elucidate the relationship of laryngeal electromyography (LEMG) and computed tomographic (CT) parameters to improve the prognosis of recurrent laryngeal nerve injury. 22 patients clinically suspected of having recurrent laryngeal nerve injury were examined with LEMG and CT studies. Bilateral thyroarytenoid (TA) muscles were examined and findings were interpreted by a single blind technique. Laryngeal CT image analysis of the ventricle dilation symmetry determined TA muscle atrophy. Finally, a follow-up laryngoscopic examination determined improvement of vocal fold movement. Ventricle dilation symmetry and the dichotomized TA muscle atrophy parameter significantly relate to the improvement of vocal fold movement (χ2 = 4.029, P = 0.039, and χ2 = 3.912, P = 0.048, respectively). When the severity of vocal fold impairment was classified as severe TA muscle atrophy or none/discrete MUAP recruitment, it was found to significantly relate with the improvement of vocal fold movement (χ2 = 6.712, P = .010). From this study, image analysis of the ventricle dilation symmetry to determine the severity of TA muscle atrophy shows promise for the improved prognosis of vocal fold immobility.